Minat Konsumen Millenial Terhadap Konsumsi Ikan Air Laut dan Ikan Air Tawar - Desy Sasri Untari; Tri Adi Wibowo; Rohmatul Anwar (Universitas Sriwijaya, 2022)
Indonesia is a country that has a larger water area than land and high potential for fishery resources. The abundance of fishery resources is not supported by high fish consumption by the community, especially the millennial generation. Interest and understanding of the benefits of consuming fish among millennials is still low. So that with the consumption patterns of different millennial generations, researchers want to know what types of fish are in great demand by the current millennial generation between seawater fish or freshwater fish that have different characteristics, especially in the Kotabumi area, North Lampung Regency. This study used interview methods and direct surveys of 100 respondents using questionnaires. The results showed that most respondents were dominated by women with a percentage of 57%, with the age range of respondents being 21-25 years and having the status of a student. The frequency of fish purchases is carried out at most five times a month and respondents prefer freshwater fish with a percentage of 69% considering that freshwater fish are fresher, easier to get and do not smell too fishy. The more popular freshwater fish species is tilapia (Oreochromis niloticus) with a percentage of 26%, while for the more purchased type of seawater fish is kitefish (Elagatis bipinnulata) amounting to 12%.